Preliminary investigation of gender assignment in 46,XY disorders of sex development with severe male undermasculinisation - Wu, D H (Zhonghua er ke za zhi = Chinese journal of pediatrics, 2019)
Objective: To explore the feasibility of gender assignment in 46,XY disorders of sex development (DSD) with severe undermasculinisation mainly based on molecular diagnosis. Methods: A retrospective study of 45 patients of 46, XY DSD with severe undermasculinisation were admitted between November 2015 and October 2018 at Children's Hospital, Zhejiang University School of Medicine. The initial social gender were all female, of whom the external genital manifestations were Prader 0 to 2; the degree of masculinity was scored using external masculinisation score (EMS); the position and development of the gonads were examined by ultrasound, cystoscopy and laparoscopy, also including assessing the development of the Wolffian tube and the Müllerian tube. The level and ratio of testosterone to dihydrotestosterone before and after hCG stimulation were evaluated for the function of Leydig cell and 5α-reductase-2. Gender role scales and sandbox games were used to assess gender role behavior. Genital sensitivity to androgen stimulation was assessed; A panel including 163 genes related to gender development were determined by second-generation sequencing in all 45 patients. Finally, a multidisciplinary team (MDT) makes a gender assignment after a comprehensive analysis mainly based on the molecular etiological diagnosis. Results: Thirty-nine out of 45 patients (87%) had an identifiable genetic etiology, and the remaining 6 (13%) were negative for genetic testing. Forty-five patients had EMS less than or equal to 3 points. Sexual psychological assessment was performed in 39 patients, with male dominance in 24 (62%) and female dominance in 15 (38%). The gender assignment was 23 cases (51%) for male and 19 cases (42%) for female, and 3 cases (7%) were not completely determined. Conclusions: Molecular diagnosis provides a strong basis for appropriate gender assignment of 46, XY DSD children with severe undermasculinisation. Based on molecular diagnosis, each DSD should be analyzed by professional MDT to analyze the clinical symptoms/signs, gonadal development, gonad tumor risk, external genital morphology, sexual psychological assessment, potential fertility opportunities, parental views, Social and cultural factors, etc. make appropriate gender assignment